2010
DOI: 10.20460/jgsm.2010415845
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personality and Being Exposed to Workplace Bullying or Mobbing

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…In this way, emotion-focused coping helps to manage emotions and to explore solutions, and both types of strategies work better jointly. Our results are aligned, as reported in previous studies [16,40].…”
Section: Discussionsupporting
confidence: 93%
“…In this way, emotion-focused coping helps to manage emotions and to explore solutions, and both types of strategies work better jointly. Our results are aligned, as reported in previous studies [16,40].…”
Section: Discussionsupporting
confidence: 93%
“…In general, to reduce negative actions of mobbing, discrimination, and violence, building honest relationships with employees based on openness and trust is essential [30]. Some organizations introduce regular meetings with employees to discuss problems and risks, while others try to listen to employees, engage in dialogue with them, and minimize distance for better communication.…”
Section: Discussion Of the Process Of Managing Psychosocial Risks Con...mentioning
confidence: 99%
“…The study concluded that 44.3% experience bullying as the victim and 19.7% of severe and middle-level reports. Deniz and Ertosun (2010) studied the relationship between the employees who are considered "victims" and workplace bullying. The study concluded that the type of personality and the one who experiences workplace bullying have a strong relationship.…”
Section: Literature Reviewmentioning
confidence: 99%